Zmiany w rozmieszczeniu pozarolniczych podmiotów gospodarczych w województwie małopolskim w latach 1999–2008 - Baran, Ewa (Przedsiębiorczość - Edukacja, 2010)
The aim of the article is to analyse the development of entrepreneurship in the Malo PolskaVoivodeship between 1999 and 2008. 22 poviats of the Malo Polska Voivodeship were studied(19 land poviats and 3 city poviats). An index was calculated in order to measure the speed ofgrowth of non rural businesses in the Malo Polska Voivodeship. The highest rate was found inthe Miechowsky (151%), Limanowsky (144%) and Wielicky poviat (142%). The lowest valuewas noted in Tarnow (106.4%).